2013
DOI: 10.1111/zoj.12073
|View full text |Cite
|
Sign up to set email alerts
|

Microgeographic differentiation among closely related species ofBiomphalaria(Gastropoda: Planorbidae) from the Andean Altiplano

Abstract: Direct development and water dependence entail limited vagility in freshwater fauna. In these organisms, the population structure is probably linked to restrictions imposed by the habitat. In this study we investigate the relative contribution of processes stimulating the divergence of populations of Biomphalaria costata (Biese, 1951) and Biomphalaria crequii (Courty, 1907), two freshwater snails occurring in two contiguous and fragmented closed basins from the Andean Altiplano using mitochondrial DNA (cytochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…Keller and Soto (1998) suggested that in this salt pan, there is no evidence of major changes in the water level in the last 12,000 years. Recently, we also detected microvicariance processes structuring the populations of the aquatic gastropod Biomphalaria crequii (Courty 1907) inhabiting the southernmost springs of the system (Collado and Méndez 2013). There is no evidence either of subterranean or surface water connection between Spring 11 and El Tatio, a geyser field located 75 km to the south in a different basin.…”
Section: Discussionmentioning
confidence: 83%
“…Keller and Soto (1998) suggested that in this salt pan, there is no evidence of major changes in the water level in the last 12,000 years. Recently, we also detected microvicariance processes structuring the populations of the aquatic gastropod Biomphalaria crequii (Courty 1907) inhabiting the southernmost springs of the system (Collado and Méndez 2013). There is no evidence either of subterranean or surface water connection between Spring 11 and El Tatio, a geyser field located 75 km to the south in a different basin.…”
Section: Discussionmentioning
confidence: 83%
“…The genetic structure of freshwater fauna confined to the Altiplano usually reflects environmental changes that fragmented previously continuous hydrological systems, changes particularly important for poorly dispersing species such as snails and amphipods (Seidel, Lang & Berg, 2009; Murphy et al, 2012). This pattern has been demonstrated at species and population level in species of snails (Collado, Vila & Méndez, 2011; Collado & Méndez, 2012a; Collado & Méndez, 2013), fishes (Keller & Soto, 1998; Morales, Vila & Poulin, 2011; Cruz-Jofré et al, 2016; Guerrero-Jiménez et al, 2017) and amphibians (Sáez et al, 2014; Victoriano et al, 2015).…”
Section: Introductionmentioning
confidence: 77%
“…The pulmonate freshwater snail Biomphalaria crequii (Courty, 1907) is co-distributed with Heleobia in a large part of the Ascotán saltpan . A genetic study carried out in this system showed that three genetic groups were present within B. crequii populations, one of them restricted to the north-central area of the saltpan, a second including snails from the south-central section, and a third from the southernmost spring (Collado & Méndez, 2013). Similarly, another molecular study revealed that the endemic killifish Orestias ascotanensis Parenti, 1984 presents high levels of genetic diversity that accounts for four differentiated groups, two located at the north and south ends and other two including several springs confined to the central area of the system being indicative of some gene flow among populations (Morales, Vila & Poulin, 2011; Cruz-Jofré et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…). Private allele and haplotype frequencies were also expected to be higher in D. deserti , because species with a more fragmented distribution should exhibit limited gene exchange among populations (Collado & Mendez ). Our mtDNA data do not support this prediction, possibly because of limited sampling per sampling locality that prevented robust estimates of private haplotype frequencies within populations (Fig.…”
Section: Discussionmentioning
confidence: 99%